Social support, psychological capital, multidimensional job burnout, and turnover intention of primary medical staff: a path analysis drawing on conservation of resources theory - Guimei Chen; Jing Wang; Qian Huang; Lingzhi Sang; Jing Yan; Ren Chen; Jing Cheng; Li Wang; Dongmei Zhang; Hong Ding (BMC, 2024)
Abstract Background Job burnout is a prevalent and emerging challenge in the primary medical system, causing mass turnover, especially of primary medical staff. Little attention has been paid to the different dimensions of job burnout (emotional exhaustion, personality disintegration, and reduced sense of achievement), which may hinder efforts to tackle high turnover intention among primary medical staff. From the perspective of conservation of resources theory, social support and psychological capital are basic resources with potential to diminish job burnout and thus lower turnover intention. However, there is insufficient research evidence on the relationships between social support, psychological capital, and the three dimensions of job burnout within the primary medical system. Objectives Focusing on primary medical staff, this study conducts a path analysis to examine the correlations between two types of resources (social support and psychological capital) and the three dimensions of job burnout, and to test the impact of the latter on turnover intention. Based on the results, effective management strategies to improve the work stability of primary medical staff are proposed. Methods Multi-stage cluster random sampling was used to select participants in Anhui Province, China. Data were collected using a self-administered questionnaire containing measures of the main variables and demographic questions. In total, 1132 valid questionnaires were returned by primary medical staff. Structural equation modeling was used for path analysis of the data. Results Social support was negatively associated with emotional exhaustion (β = − 0.088, P = 0.020), personality disintegration (β = − 0.235, P < 0.001), and reduced sense of achievement (β = − 0.075, P = 0.040). Moreover, psychological capital was negatively associated with emotional exhaustion (β = − 0.079, P = 0.030), personality disintegration (β = − 0.156, P < 0.001), and reduced sense of achievement (β = − 0.432, P < 0.001). All three dimensions of job burnout positively affected turnover intention (emotional exhaustion: β = 0.246, P < 0.001; personality disintegration: β = 0.076, P = 0.040; reduced sense of achievement: β = 0.119, P = 0.001). Conclusions The results highlight the importance of social support and psychological capital for diminishing the three dimensions of job burnout for primary medical staff and, in turn, lowering their turnover intention. Accordingly, to alleviate job burnout and improve staff retention, material and psychological supports from leaders, colleagues, family, relatives, and friends are essential, as are measures to improve the psychological energy of primary medical staff.